Whole-Genome Sequencing of Human and Porcine Escherichia coli Isolates on a Commercial Pig Farm in South Africa - Wilhelmina Strasheim; Michelle Lowe; Anthony M. Smith; Eric M. C. Etter; Olga Perovic (MDPI AG, 2024)
Escherichia coli is an indicator micro-organism in One Health antibiotic resistance surveillance programs. The purpose of the study was to describe and compare E. coli isolates obtained from pigs and human contacts from a commercial farm in South Africa using conventional methods and whole-genome sequencing (WGS). Porcine E. coli isolates were proportionally more resistant phenotypically and harbored a richer diversity of antibiotic resistance genes as compared to human E. coli isolates. Different pathovars, namely ExPEC (12.43%, 21/169), ETEC (4.14%, 7/169), EPEC (2.96%, 5/169), EAEC (2.96%, 5/169) and STEC (1.18%, 2/169), were detected at low frequencies. Sequence type complex (STc) 10 was the most prevalent (85.51%, 59/169) among human and porcine isolates. Six STcs (STc10, STc86, STc168, STc206, STc278 and STc469) were shared at the human-livestock interface according to multilocus sequence typing (MLST). Core-genome MLST and hierarchical clustering (HC) showed that human and porcine isolates were overall genetically diverse, but some clustering at HC2-HC200 was observed. In conclusion, even though the isolates shared a spatiotemporal relationship, there were still differences in the virulence potential, antibiotic resistance profiles and cgMLST and HC according to the source of isolation.